2019
DOI: 10.3389/fmicb.2019.02790
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole Increases the Efficacy of Acyclovir Against Herpes Simplex Virus Type 1 and 2

Abstract: Omeprazole was shown to improve the anti-cancer effects of the nucleoside analogue 5-fluorouracil. Here, we combined omeprazole with the antiviral nucleoside analogues ribavirin and acyclovir. Omeprazole did not affect the antiviral effects of ribavirin in non-toxic concentrations up to 80 μg/mL but increased the acyclovir-mediated effects on herpes simplex virus 1 and 2 (HSV-1 and -2) replication in a dose-dependent manner. Omeprazole alone reduced HSV-1 and -2 titers [but not HSV-induced formation of cytopat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…They have been suggested as treatment options and conversely as risk factors [ 42 ] for COVID-19. However, there are studies that support their inhibitory effects on infectious agents that are frequently found in COVID-19 coinfections like HSV-1/ HSV-2 [ 43 ] and Candida albicans [ 44 ]. Whether the use of these drugs is beneficial or detrimental to COVID-19 patients needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…They have been suggested as treatment options and conversely as risk factors [ 42 ] for COVID-19. However, there are studies that support their inhibitory effects on infectious agents that are frequently found in COVID-19 coinfections like HSV-1/ HSV-2 [ 43 ] and Candida albicans [ 44 ]. Whether the use of these drugs is beneficial or detrimental to COVID-19 patients needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Omeprazole was found to increase the anti-cancer effect of nucleoside analog 5-fluorouracil without affecting ribavirin in nontoxic concentration (up to 80 mg/mL). Instead, it enhances the acyclovir-mediated effect on HSV-1 & 2 [155]. Moreover, a newly synthesized compound 2pyrimidyl benzothiazole derivatives exhibit antiviral activities and inhibitory effect on Hsp90α protein.…”
Section: Current Status and Future Prospects Of Hsv-1 Researchmentioning
confidence: 98%
“…96 (6) 1 AvDs exhibited anti-HSV effects. NA-AvD acyclovir 88 was activated by viral thymidine kinase and then di-and tri-phosphorylated by cellular kinases. The active tri-phosphorylated forms of acyclovir specifically interfered with viral DNA polymerase and caused chain termination.…”
Section: Pharmacological Activity Of Avds and Their Delivery Systems Pharmacological Activity Of Avdsmentioning
confidence: 99%
“…The active tri-phosphorylated forms of acyclovir specifically interfered with viral DNA polymerase and caused chain termination. 88…”
Section: Pharmacological Activity Of Avds and Their Delivery Systems Pharmacological Activity Of Avdsmentioning
confidence: 99%